Lipid profile in pre-eclampsia and normal pregnancy - Jagannath Patar; Nilabh Acharjee (New Indian Journal of OBGYN)
Background: Pre-eclampsia is globally a cause of maternal and fetal morbidity and mortality. Hence, it is important to study the lipid profile and risk factors for prevention, management and prognosis of the disease. Objectives: Present study was conducted to observe differences between normal and preeclampsia lipid profiles. Method and materials: A case control study was conducted in the Obstetrics and Gynaecology department, Tezpur Medical college, Tezpur, Assam from March 2022 to February 2023. In this study 100 cases were selected, out of which 50 normotensive pregnant women as a control and 50 pre-eclampsia women as study group. All routine baseline investigations, serum lipid profile estimation was done by collecting blood samples from antecubital veins from every case and control following a fast of 12 - 14 hours in plain vials and then analyzed in the department of Biochemistry, Tezpur Medical college, Tezpur. Results: It was found that mean ± SD of triglyceride (224.30±38.41 mg/dl), total cholesterol (206.82±29.89 mg/dl) and LDL cholesterol (119.94±20.24 mg/dl) among the women in the study group was higher than the mean ± SD of triglycerides (178.06±21.0 mg/dl2), total cholesterol (166.64±18.80 mg/dl) and LDL cholesterol (90.22±15.41 mg/dl) among women in the control group. Again, mean ± SD of HDL cholesterol among the study group was lower than the mean ± SD of HDL cholesterol among the control group. Statistically, there is a significant difference in case of triglycerides, total cholesterol, HDL - cholesterol and LDL- cholesterol. Conclusion: Abnormal lipid profile during pregnancy plays an important role in the development of Pre-eclampsia.